A study on the high fluoride concentration in the magnesium-rich waters of hard rock aquifer in Krishnagiri district, Tamilnadu, India - Manikandan, S.; Chidambaram, S.; Ramanathan, A.; Prasanna, Mohan Viswanathan; Karmegam, U.; Singaraja, C.; Paramaguru, P.; Jainab, I. (Springer, 2014)
Excess fluoride in groundwater affects the human health and results in dental and skeletal fluorosis. Higher concentration of fluoride was noted in hard rock terrain of the south India, in the Krishnagiri district of Tamilnadu. The region has a complex geology ranging from ultra basic to acid igneous rocks, charnockite and gneissic rocks. Thirty-four groundwater samples were collected from this study area and analysed for major cations and anions along with fluoride. The order of dominance of cations is Na+ > Mg2+ > Ca2+ > K+ and the anions in the following order HCO3 − > Cl− > NO3 − > SO4 2−. It is found that nearly 58 % of the samples have more fluoride ranging from 1 to 3 mg/L. It is also noted that high fluoride waters correspond to magnesium water types. This is due to the release of fluoride from the magnesium-bearing minerals like, biotite, hornblende, etc., or weathering of apatite/hydroxyapatites found in charnockites.